In Silico and In Vitro Comparison of HIV-1 Subtypes B and CRF02_AG Integrases Susceptibility to Integrase Strand Transfer Inhibitors - Ni, Xiaoju (Hindawi Publishing Corporation, 2012)
Most antiretroviral medical treatments were developed and tested principally on HIV-1 B nonrecombinant strain, which represents less than 10% of the worldwide HIV-1-infected population. HIV-1 circulating recombinant form CRF02_AG is prevalent in West Africa and is becoming more frequent in other countries. Previous studies suggested that the HIV-1 polymorphisms might be associated to variable susceptibility to antiretrovirals. This study is pointed to compare the susceptibility to integrase (IN) inhibitors of HIV-1 subtype CRF02_AG IN respectively to HIV-1 B. Structural models of B and CRF02_AG HIV-1 INs as unbound enzymes and in complex with the DNA substrate were built by homology modeling. IN inhibitors—raltegravir (RAL), elvitegravir (ELV) and L731,988—were docked onto the models, and their binding affinity for both HIV-1 B and CRF02_AG INs was compared. CRF02_AG INs were cloned and expressed from plasma of integrase strand transfer inhibitor (INSTI)-naïve infected patients. Our in silico and in vitro studies showed that the sequence variations between the INs of CRF02_AG and B strains did not lead to any notable difference in the structural features of the enzyme and did not impact the susceptibility to the IN inhibitors. The binding modes and affinities of INSTI inhibitors to B and CRF02_AG INs were found to be similar. Although previous studies suggested that several naturally occurring variations of CRF02_AG IN might alter either IN/vDNA interactions or INSTIs binding, our study demonstrate that these variations do affect neither IN activity nor its susceptibility to INSTIs.